HUBUNGAN ANTARA MOTIVASI YANG DIBERIKAN ORANG TUA DENGAN HASIL BELAJAR SISWA KELAS III GUGUS BOUGENVILLE UPTD TENAYAN RAYA - Nurmaida Nurmaida '; Syahrilfuddin Syahrilfuddin '; Hamizi Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research starts from the observation of researchers who see a different value on each student learning outcomes, researchers looked for differences in the spirit of learning from students at school. This is presumably due to a lack of motivation given their parents. This study was done to determine the relationship between motivation given parents the learning outcomes of students of class III group Bougenville UPTD Tenayan highway conducted in 4 schools SDN 46 Pekanbaru, Pekanbaru SDN 186, 171 SDN and SDN 146 Pekanbaru Pekanbaru. This research is a correlation study (Study correlational) or correlation study. Population in this research were 367 students, using systematic sampling technique that uses multiples of 4 then didapatlah sample of 87 students. The instruments used by researchers to collect data that is using a questionnaire first tested the validity and reliability by using SPSS version 17.0. to test the normality of the data, researchers used a test Lilliefors test. Furthermore, to megetahui relationship between motivation given parent (X) with student learning outcomes (Y) used Peasrsn Product Moment Correlation formula. From the analysis of the data is obtained no significant relationship between motivation provided parents with learning outcomes Civics, Indonesian, science, social studies, and math students in grade III group Bougenville UPTD Tenayan highway where the Civics obtained Thitung ≥ Ttabel = 3.670 ≥ 1.671 with a contribution of 13.69%, the Indonesian obtained Thitung ≥ Ttabel = 3.699 ≥ 1.671 with a contribution of 13.91%, in Mathematics obtained Thitung Ttabel = 2,35 ≥ ≥ 1.671 with a contribution of 6.10%, the IPS obtained Thitung ≥ Ttabel = 5.068 ≥ 1.671 with a contribution of 23.23%, and the IPA gained ≥ Thitung Ttabel = 3.772 ≥ 1.671 with a contribution of 14.36%.Keywords: Motivation Provided Parent, Student Results